Title:

Author:

M1 Basics

Copyright:

T. Tsujioka

Advanced Seminar

__M1 Basics__

Chapter 4. Systems of Simultaneous Equations

4-1. By Substitution Method

Consider solving the following simultaneous equations:Form (1), we have *x* = 3 −2*y*. If this *x* is substituted into (2), we obtain:

3(3 −2*y*) − 4*y* = −1 ⇔ 9 −10*y* = −1,

from which we can solve for *y*:

*y* = 1.

Then, substituting this value into (1) or (2), we obtain *x*:

*x* = 1.

Ans. *x* = 1, *y* = 1.

[You may write as (*x*, *y*) = (1, 1) as long as the answer is shown without ambiguity.]